Russian perspectives - Torelli, Giuseppe 1658-1709; Čajkovskij, Pëtr Ilʹič 1840-1893; Rachmaninov, Sergej Vasilʹevič 1873-1943; Rubinštejn, Anton G. 1829-1894; Gedike, Fëdor Karlovič 1839-1916; Honegger, Arthur 1892-1955; Hindemith, Paul 1895-1963; Enescu, George 1881-1955; Martini, Giovanni Battista 1706-1784; Giazotto, Remo 1910-1998; Mozart, Wolfgang Amadeus 1756-1791 (International Trumpet Guild journal, 2015)
The disc in your hands is a compendium of recordings done between 1959 and 2011 by the outstanding Russian trumpeter Vadim Novikov (b. 1941), whose longtime professional activities have been focused on establishing the trumpet as a solo instrument and as a consistent participant in the concert life of Russia. - Container